Effectiveness of the Combination of Raffia Rope Attractors and Lighting on Fish Aggregating Devices (FADs) for Positive Phototactic Fish - Rizky Janatul Magwa; Farhan Ramdhani; Yoppie Wulanda (Grouper, 2026)
Fish Aggregating Devices (FADs) are widely used to improve fishing efficiency, and their effectiveness depends largely on attractor design and visual stimuli such as light. This study aimed to evaluate the effectiveness of combining raffia rope attractors and LED lighting on surface FADs in attracting positive phototactic fish (Poecilia reticulata), and to assess their vertical distribution and behavioral responses. A laboratory experiment was conducted using a factorial Completely Randomized Design (position × light presence) with four treatments: bottom without light, bottom with light, surface without light, and surface with light. The primary parameter measured was the number of fish within a 10 cm attraction zone, recorded every 10 minutes for 60 minutes. Data were analyzed using Two-Way ANOVA at a 5% significance level. The results showed that FAD position significantly affected the number of fish approaching the attraction zone (p < 0.05), whereas light presence alone had no significant effect (p > 0.05). However, a significant interaction between position and light was detected (p < 0.05). The highest effectiveness was observed in the surface FAD without light (77%), suggesting that the visual structure of raffia attractors at the surface was sufficient to induce strong aggregation. These findings indicate that the effectiveness of raffia attractors is primarily driven by placement position rather than additional lighting, although their interaction still contributes to fish aggregation behavior. This study provides a practical basis for prioritizing surface FAD placement with raffia attractors over the use of additional lighting in small-scale fisheries.